IMPLEMENTASI PRAKTIK PENDATAAN KEPENDUDUKAN OFLINE MAHASISWA KKN-PPM UNIVERSITAS PGRI ADI BUANA SURABAYA DI DESA BULANG PRAMBON SIDOARJO - Intan Kusuma Pramusinta (Jurnal Abadimas Adi Buana, 2017)
Documenting the population is something that is very very important for each village. because every village in definite need of complete data from the start of births, deaths and the displacement of each population. A large number of residents in a village will be very high in the village administrative irregularities such as population data etc. By mindless, we KKN PPM students Adi Buana University PGRI Surabaya tried to present the latest innovations for data collection on the population of a village to be more organized and structured. That is by using the application of unisoft. This application will make it easier for the village to look for and create data villagers, manufacture and maintenance of correspondence family card. In addition to demographic data collection is also our online mapping the form of making a village map that is useful to know the location-graphic layout of the village. Our way to introduce the modern-based applications to the village is by directing the secretary of the village and its ranks against unisof applications. our hope they can use this application with wise and appropriate. the results seen in the last month when we menjankan corruption in the village of Bulang Prambon. with piecemeal village books organized and easy to manufacture letters associated with the village.